JOSEPH RYKWERT - Remembering Places. A Memoir - Díez Medina, Carmen (ZARCH, 2025)
JOSEPH RYKWERT Remembering Places. A Memoir Routledge, Londres, 2017, 198 pp. Tapa blanda. £35.99 Idioma: inglés ISBN-10: ‎ 9781138242470 ISBN-13: ‎ 978-1138242470